2022
DOI: 10.1002/jso.26898
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for local atypical fibroxanthoma recurrence and progression to pleomorphic dermal sarcoma: A meta‐analysis of individualized participant data

Abstract: Background Risk factors for local atypical fibroxanthoma (AFX) recurrence and progression to pleomorphic dermal sarcoma (PDS) have not previously been identified. Objective To identify risk factors and provide follow‐up suggestions for local AFX recurrence and progression to PDS. Methods and Materials A literature search was performed in the PubMed, EMBASE, and Cochrane databases. The PRISMA and MOOSE guidelines were followed. The risks of local AFX recurrence and progression to PDS were presented as Kaplan–Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A recent meta-analysis of 598 patients noted a 1-year recurrence risk of 3.2%, which is lower than our cohort, but the 5 year recurrence rate was much higher at 7.3%. 27 The final limitation is the inability to run statistical analysis via the cox-regression.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 598 patients noted a 1-year recurrence risk of 3.2%, which is lower than our cohort, but the 5 year recurrence rate was much higher at 7.3%. 27 The final limitation is the inability to run statistical analysis via the cox-regression.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with AFX usually experience a more benign clinical course with risks limited to local recurrence, whereas PDS is considered more invasive and aggressive due to a high risk of local recurrence and metastases. [1][2][3][4] The main features that differentiate PDS from AFX are deep invasion of the subcutis, tumor necrosis, and vascular, perineural, or perilymphatic invasion. 1,5,6 Currently, there are no reliable discriminatory immunomarkers that distinguish AFX from PDS.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with AFX usually experience a more benign clinical course with risks limited to local recurrence, whereas PDS is considered more invasive and aggressive due to a high risk of local recurrence and metastases. 1–4…”
Section: Introductionmentioning
confidence: 99%
“…However, very few retrospective studies have compared these 2 surgical modalities, and some did not find meaningful differences in the rates of recurrence. 2 The aim of this study was to compare the rates of recurrence and survival between MMS and WLE for AFX.…”
mentioning
confidence: 99%
“…Furthermore, our univariate analysis showed that higher comorbidity scores were associated with recurrence, while prior reports suggest that ages >74 and male sex are also risk factors for recurrence. 2 …”
mentioning
confidence: 99%